Analytical Model and Solution Illustrating Classical Optical Contribution to Giant Spectral Splitting in Strongly-Coupled Micro/nanocavity-atom System - Zeng, Jian; Li, Zhi-Yuan (Frontiers in Physics, 2022)
Many experimental observations have shown remarkably large or even giant spectral splitting in strongly-coupled micro/nanocavity-atom systems. Popularly, such a spectral splitting has been attributed to the Rabi splitting, a pure quantum mechanical effect. However, there are disputes regarding whether the spectral splitting caused by multiple emitters, such as excitons in J-aggregate of molecules, is a pure quantum effect or also contributed by classical optical effect. In this work, we address this difficult problem by building a model physical system of a practical Fabry-Perot high-Q optical microcavity involving Lorentz-dispersion atoms. Very interestingly, by performing evaluation and estimate upon several strongly-coupled cavity-atom systems, we have found that the classical optical splitting and quantum Rabi splitting can be in the same order of magnitude. Our studies clearly indicate that the phenomenon of "giant Rabi splitting" that has been extensively observed in many experiments can also be caused by classic optical effects in addition to quantum mechanical effect. In some cases, the contribution by classic optical effects may be comparable to or even exceeding the contribution from quantum effects. We expect that this work can constructing the true and complete physics picture underlying strong light-matter interaction in a micro/nanocavity system.